MC-Sim: a mobile cloud simulation toolkit based on CloudSim. (2018) - Gherari, Manel; Amirat, Abdelkrim; Laouar, Mohamed Ridda; Oussalah, Mourad
Mobile Cloud Computing (MCC) has gained a significant attention these past years. MCC consists of migrating mobile applications from the constrained mobile devices to the cloud. This task is highly complicated and demanding, therefore several novel methods, tools, and approaches are introduced to tackle this complexity. At this point, we argue that a simulation of the deployment mechanisms for accessing cloud services and testing mobile cloud applications in the cloud environment is a mandatory phase prior to real deployment in a real environment. A simulation will offer the developer a controllable and cost-free environment to test and evaluate applications' performance according to different predefined scenarios. As MCC lacks tools of simulation of its aspects, to fill this gap we propose Mobile Cloud Simulation (MC-Sim) toolkits based on CloudSim.